The answers are
M1 = 112°
M2 = 26°
Answer:
The answer is 4
Step-by-step explanation:
2/3 x 6= 4
2x - 6 = 18
2x = 18 + 6 (24)
2x = 24
x = 12
<span>3x + 9 = 2x + 24
3x + 9 = 2x + 24 - 9 (2x + 15)
3x = 2x + 15
3x - 2x = 15
x = 15
</span><span>4x = 2.4? 0.4x = 2.4? I can't tell what the question is. Let me know in the comments and I'll answer it.
</span>
<span>5x + 4 = 24
5x = 24 - 4 (20)
5x = 20
x = 4
</span><span>2x / 3 = 4
2x = 4 * 3 (12)
x = 6
</span><span>3(x + 7) = 51
3x + 21 = 51
3x = 51 - 21 (30)
3x = 30
x = 10
Hope I helped :)</span>
The difference of the expression is as follows:
(6y⁴ + 3y² - 7) - (12y⁴ - y² + 5) = - 6y⁴ + 4y² - 12
3(x - 5) - (2x + 4) = x - 19
<h3>How to find the difference of the expression?</h3>
The difference of the expression can be found when we combine the like terms.
Therefore,
(6y⁴ + 3y² - 7) - (12y⁴ - y² + 5)
6y⁴ + 3y² - 7 - 12y⁴ + y² - 5
6y⁴ - 12y⁴ + 3y² + y² - 7 - 5
- 6y⁴ + 4y² - 12
3(x - 5) - (2x + 4)
3x - 15 - 2x - 4
3x - 2x - 15 - 4
x - 19
learn more on expression here: brainly.com/question/14294918
#SPJ1